Transfer and diagnosis of acute neonatal cardiac cases, lessons from embrace - a new transport service. (24th May 2012) - Kashyap, A S; Oruganti, S; Hancock, S W; Harrison, C M; Newbegin, R; Thomson, J
Abstract : Introduction: Understanding the current flow of acute neonatal cardiac patients has important implications for patient safety and the future development of services. Embrace, Yorkshire and Humber Infant and Children's Transport Service is the UK's first combined neonatal and paediatric team providing a comprehensive service across an entire region and is well placed to provide such information. Aim: Evaluation of all Embrace transfers of patients locally identified as potentially duct dependent from local hospitals in Yorkshire and Humber region into the tertiary unit in Leeds. Methods: Retrospective case review over a 12-month period (April'10 – April'11) from the Embrace database. Results: Of 2323 transfers, 198 (8.5%) were cardiac (74 paediatric, 124 neonatal). 34 patients were identified with potentially duct dependent lesions at their referring institution. ▶ Local echocardiographic diagnosis was attempted in 14/34 (41%) patients of whom the diagnosis proved correct in 9/14 (64%). ▶ Median mobilisation time (referral call to departure from base) 42 minutes (15-116). ▶ Median time from referral call to arrival at cardiac centre 276 minutes (104-468). Conclusion: Cardiac transfers constitute a significant proportion of current transport workload. Early data indicates approximately 200 (30-40 duct dependant) cardiac cases will need transfer per annum in the region currently taking an average of 4.6 hours to reach the tertiary centre. Despite a well-established network the proportion of babies with an adequate diagnosis at transfer is disappointing. Transport logistics and local cardiology services for this patient group remains an issue going forward with the national cardiac review.